Ecology and diversity of Cortinarius species (Agaricales, Basidiomycota) associated with Quercus ilex L. in the Mediterranean area of Liguria (North-western Italy) - Zotti, M; Ambrosio, E; Di Piazza, S; Bidaud, A; Boccardo, F; Pavarino, M; Mariotti, M G; Vizzini, A (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
Cortinarius is one of the most widespread macrofungal genera. Although Mediterranean basin is considered a biodiversity hotspot, very few studies have addressed the presence and importance of Cortinarius species in such area. Surveys were carried out in Liguria (NW Italy) in different habitats characterized by the presence of Quercus ilex. Altogether 67 taxa were observed: 49 of them are new records for Liguria while 23 represent new records for Italy. In addition, we report the distinguishing characters and ecological traits of the species which are also rare in Europe.
doi: 10.1080/11263504.2013.877538
Keywords: Agaricomycetes; Biodiversity; conservation; Cortinariaceae; holm-oak; Macrofungi